Effect of basic motivational factors on construction workforce productivity in Turkey/Pagrindinių motyvacijos veiksnių įtaka statybos produktyvumui Turkijoje - Aynur Kazaz (Journal of Civil Engineering and Management, 2008)
Human resource today has a strategic role for productivity increase of any organization, and this makes it superior in the industrial competition. With the effective and optimum usage of it, all the advantages supplied by the productivity growth can be obtained. This usage is just possible by establishing clear and understandable criteria for the factors affecting labour. Therefore, it is aimed in this study that the factors influencing construction labour productivity in Turkey are determined, defined, and examined in detail. A survey was applied to 82 firms to obtain required data. According to results, the most effective factors group is organizational factors.